(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
Does the Behavior Analysis have theoretical and empirical support to explain language development and learning? To answer this question, we summarized four theoretical analytical-behavioral perspectives on the acquisition and development of the language: Verbal Behavior; Symbolic Behavior; Naming Theory; Relational Frame Theory. This study aimed to present convergences and divergences between those theoretical perspectives and to present the implications for the conduction of empirical studies with participants children up to 36 months, usually named young children. From the Skinner’s proposal of analysis of verbal behavior there were advances in theories that tried to fill gaps in the explanation of the development and initial acquisition of the language. It is argued that it is necessary to expand the researches that describe the early acquisition of verbal and symbolic repertoires of children, in experimental context and in the natural environment, to give the necessary empirical support to the theoretical formulations.